"As Old as War Itself"? Historicizing the Universal Mercenary. Issue 1 (26th February 2020) - Riemann, Malte
Abstract: IR scholarship has increasingly begun to scrutinize the ahistorical and ahistoricist assumptions pervading the discipline. Specifically, attention has been turned to those concepts, actors, and practices that appear to be without history and that therefore assumed the status of universals. This article contributes to this scholarship by critically investigating the seemingly transhistorical figure of the mercenary, whose history, it appears, is little less than the history of organized warfare itself. This article questions this assumption by investigating how the Renaissance Landsknechte, actors invoked to support the transhistorical mercenary claim, were problematized within their own historical specificity. Through this analysis, this article rejects the notion that the mercenary is a transhistorical phenomenon as the ideas and categories associated with this figure are tied to specific modern accounts of statist political community and individual identity, as well as a modern account of self-interest. It is argued that the mercenary is not a phenomenon that predates the emergence of the modern state and the system of states, but its own existence is grounded within them. This article, thus, reinstates the historicity of this figure and argues that the mercenary is not "as old as war itself" but a product of specific modern conditions.